The testing of Abraham in Genesis 22 and the testing of Job - S Fischer (Acta Theologica)
This article analyses and compares the testing of Abraham and that of Job. The analysis of Genesis 22 examines the meaning of God testing Abraham in comparison to other instances of God testing individuals in the Bible and draws parallels with the book of Job. Both positive and negative interpretations of human sacrifice are considered with reference to Jewish sources. The tension between the narrative and the poetic part of the book of Job is understood as a correction of a fatalistic, obedient world view. Such critical thinking is lacking in Genesis 22 and is only part of the reception history.